Misfolded SOD1 inclusions in patients with mutations in C9orf72 and other ALS/FTD-associated genes. Issue 8 (16th April 2019) - Forsberg, Karin; Graffmo, Karin; Pakkenberg, Bente; Weber, Markus; Nielsen, Martin; Marklund, Stefan; Brännström, Thomas; Andersen, Peter Munch
Abstract : Objective: A hallmark of amyotrophic lateral sclerosis (ALS) caused by mutations in superoxide dismutase-1 ( SOD1 ) are inclusions containing SOD1 in motor neurons. Here, we searched for SOD1-positive inclusions in 29 patients carrying ALS-linked mutations in six other genes. Methods: A panel of antibodies that specifically recognise misfolded SOD1 species were used for immunohistochemical investigations of autopsy tissue. Results: The 18 patients with hexanucleotide-repeat-expansions in C9orf72 had inclusions of misfolded wild type (WT) SOD1 WT in spinal motor neurons. Similar inclusions were occasionally observed in medulla oblongata and in the motor cortex and frontal lobe. Patients with mutations in FUS, KIF5A, NEK1, ALSIN or VAPB, carried similar SOD1 WT inclusions. Minute amounts of misSOD1 WT inclusions were detected in 2 of 20 patients deceased from non-neurological causes and in 4 of 10 patients with other neurodegenerative diseases. Comparison was made with 17 patients with 9 different SOD1 mutations. Morphologically, the inclusions in patients with mutations in C9orf72HRE, FUS, KIF5A, NEK1, VAPB and ALSIN resembled inclusions in patients carrying the wildtype-like SOD1 D90A mutation, whereas patients carrying unstable SOD1 mutations (A4V, V5M, D76Y, D83G, D101G, G114A, G127X, L144F) had larger skein-like SOD1-positive inclusions. Conclusions and relevance: Abundant inclusions containing misfolded SOD1 WT are found in spinal and cortical motor neurons in patients carrying mutations in six ALS-causing genes other than SOD1 . This suggests that misfolding of SOD1 WT can be part of a common downstream event that may be pathogenic. The new anti-SOD1 therapeutics in development may have applications for a broader range of patients.